An investigation of the energy storage properties of a 2D α-MoO3-SWCNTs composite films. (26th October 2016) - Mendoza-Sánchez, Beatriz; Hanlon, Damien; Coelho, João; Brien, Sean O'; Pettersson, Henrik; Coleman, Jonathan; Nicolosi, Valeria
Abstract: We recently reported on the synthesis of 2D α -MoO3 using a scalable liquid-phase exfoliation method, its characterization and preliminary studies of its potential for energy storage applications [1 ]. The material was examined in a LiClO4 /propylene carbonate electrolyte, and in a 1.5–3.5 V versus Li + /Li electrochemical window [1 ]. The charge storage of 2D α -MoO3 electrodes was negligible and this was attributed to electrical limitations imposed by the semiconducting nature of 2D α -MoO3 . Electrical conductivity studies of 2D α -MoO3 /SWCNT electrodes, where a fraction of SWCNTs was progressively added, led to finding the SWCNT fraction for which an electrical percolation threshold was reached, i.e. a sharp increase of electrical conductivity. This SWCNT fraction also led to a sharp increase in capacitance confirming the electrical limitation of charge storage. In this work, we examined in detail the energy storage properties of 2D α -MoO3 /SWCNT (85 wt%/15 wt%) electrodes. A detailed study of ion-intercalation events, as examined by cyclic voltammetry, is presented. We investigated the contributions to the overall energy storage of capacitive and diffusion-controlled processes and how the performance compares against other nanostructured materials including mesoporous α -MoO3 and α -MoO3 nanobelts. Our main findings showed that 2D α -MoO3 /SWCNT (85 wt%/15 wt%) electrodes offer scope for supercapacitors and battery applications in terms of total charge storage (200 F g −1 and 195.2 mAh g −1 ), which is in the range or superior to that of other nanostructured metal oxides and commercial LiCoO2 cathodes. However, a main drawback is cycling stability.